Technological approaches (operational schema) (Scottish Historical and Archaeological Internet Reports, 2008)
This discussion of the technological aspects of quartz production presents Scottish quartz in terms of its operational schema as experienced through the available assemblages. It considers procurement (embedded, direct and indirect), core preparation and rejuvenation, blank production, tool production and symbolic values.